Morphological features of histogenic differon cells in connective tissue of guinea pigs’ lungs after sensitization with ovalbumin - Popko, S. S.; Yevtushenko, V. M.; Попко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна; Попко, С. С.; Евтушенко, В. М. (Запорізький державний медичний університет, 2021)
An urgent issue of modern morphology is establishing a number of patterns of morphological changes and reactivity of connective tissue components of lungs in case of experimental sensitization with allergens. The aim is to estimate morphological features of histogenic differon cells in connective tissue of guinea pigs’ lungs after sensitization with ovalbumin. Materials and methods. Using morphometric and histological method, we have estimated the lung connective tissue of 48 male guinea pigs with experimental ovalbumin-induced allergic inflammation, simulated by subcutaneous sensitization and aeroallergization with ovalbumin. The number of fibrocytes, fibroblasts per 5000 μm2 and their ratio – fibroblast/fibrocyte coefficient were determined. Results. We have established the regularity of morphological changes dynamics in the cellular elements of pulmonary connective tissue. Experimental sensitization and inhalated allergization with ovalbumin leads to a statistically significant increase in the average number of fibroblasts and fibrocytes throughout the observation period in all experimental groups. It has been proved that the dynamics of cells has a multidirectional character, demonstrated by indicators of the fibroblast/fibrocyte coefficient, which shows the disproportion in the fibroblast/fibrocyte ratio and proves the tendency to the development of fibrosis in guinea pigs’ pulmonary connective tissue in case of experimental sensitization with ovalbumin. Conclusions. A gradual increase in the number of fibrocytes, against the background of a decrease in the number of fibroblasts is observed from the 23rd day to the completion of experimental sensitization with ovalbumin in the lungs of guinea pigs, compared with control group. A decrease of fibroblast/fibrocyte coefficient from 1.37 ± 0.03 in the early period to 0.82 ± 0.03 in the late period of the allergic inflammation demonstrates multidirectional nature of the dynamics in the number of connective tissue cells and indicates a tendency towards the development of fibrosis in pulmonary connective tissue. Актуальною проблемою сучасної морфології є питання щодо встановлення низки закономірностей морфологічних змін і реактивності компонентів сполучної тканини легень при експериментальній сенсибілізації алергенами. Мета роботи – з’ясувати морфологічні особливості клітин гістогенного диферону сполучної тканини легень морської свинки після сенсибілізації овальбуміном. Матеріали та методи. Використовуючи морфометричний і гістологічний методи, дослідили сполучну тканину легень 48 самців морської свинки з експериментальним алергічним запаленням, змодельованим сенсибілізацією та аероалергізацією овальбуміном. Визначали середню кількість фіброцитів, фібробластів на умовну одиницю площі 5000 мкм2 та їхнє співвідношення – фібробластно-фіброцитарний коефіцієнт. Результати. Встановили закономірність динаміки морфологічних змін клітинних елементів сполучної тканини легень. Експериментальна сенсибілізація та інгаляційна алергізація овальбуміном призводять до статистично значущого збільшення середньої кількості фібробластів і фіброцитів протягом усіх термінів спостереження в усіх експериментальних групах. Динаміка клітин має різноспрямований характер, що підтверджено показниками фібробластно-фіброцитарного коефіцієнта, які свідчать про диспропорційність у співвідношенні фібробласти/фіброцити, показують тенденцію до розвитку фіброзу та склеротичних процесів у сполучній тканині легень морських свинок під час експериментальної сенсибілізації овальбуміном. Висновки. Від 23 до 44 доби після початку експериментальної сенсибілізації овальбуміном у легенях морських свинок порівняно з контролем спостерігали поступове збільшення середньої кількості фіброцитів, але зменшення середньої кількості фібробластів. Різноспрямований характер у динаміці кількості клітин сполучної тканини показує зменшення показника фібробластно-фіброцитарного коефіцієнта від 1,37 ± 0,03 в ранньому періоді до 0,82 ± 0,03 в пізньому періоді розвитку алергічного запалення, що свідчить про тенденцію до розвитку фіброзу в сполучній тканині легень морської свинки. Актуальная проблема современной морфологии – вопрос об установлении ряда закономерностей морфологических изменений и реактивности компонентов соединительной ткани лёгких при экспериментальной сенсибилизации аллергенами. Цель работы – установить морфологические особенности клеток гистогенного дифферона соединительной ткани лёгких морских свинок после сенсибилизации овальбумином. Материалы и методы. Используя морфометрический и гистологический методы, исследовали соединительную ткань лёгких 48 самцов морской свинки с экспериментальным аллергическим воспалением, смоделированным сенсибилизацией и аэроаллергизацией овальбумином. Определяли среднее количество фиброцитов, фибробластов на условную единицу площади 5000 мкм2 и их соотношение – фибробластно-фиброцитарный коэффициент. Результаты. Установлена закономерность динамики морфологических изменений клеточных элементов соединительной ткани лёгких. Экспериментальная сенсибилизация и ингаляционная аллергизация овальбумином приводят к статистически значимому увеличению среднего количества фибробластов и фиброцитов на протяжении всех сроков наблюдения во всех экспериментальных группах. Динамика клеток имеет разнонаправленный характер, который отражают показатели фибробластно-фиброцитарного коэффициента, свидетельствующие о диспропорции в соотношении фибробласты/фиброциты и являющиеся подтверждением тенденции к развитию фиброза и склеротических процессов в соединительной ткани лёгких морских свинок при экспериментальной сенсибилизации овальбумином. Выводы. С 23 по 44 сутки после начала экспериментальной сенсибилизации овальбумином в лёгких морских свинок по сравнению с контролем отмечено постепенное увеличение среднего количества фиброцитов, но уменьшение среднего количества фибробластов. Уменьшение показателя фибробластно-фиброцитарного коэффициента с 1,37 ± 0,03 в раннем периоде до 0,82 ± 0,03 отражает разнонаправленный характер в динамике количества клеток соединительной ткани в позднем периоде развития аллергического воспаления, свидетельствует о тенденции к развитию фиброза в соединительной ткани лёгких морских свинок.
Морфологічні особливості клітин гістогенного диферону сполучної тканини легень після сенсибілізації овальбуміном
Морфологические особенности клеток гистогенного дифферона соединительной ткани лёгких после сенсибилизации овальбумином
Попко С. С. - ORCID ID: 0000-0002-5533-4556
Keywords: guinea pigs; fibrocyte; fibroblasts; pulmonary connective tissue; experimental allergic inflammation; ovalbumin; морська свинка; фіброцит; фібробласт; сполучна тканина легень; експериментальне алергічне запалення; овальбумін; морская свинка; фиброцит; фибробласт; соединительная ткань лёгких; экспериментальное аллергическое воспаление; овальбумин